Teaching English in a Cross-cultural Context: Challenges and Directions - Sultana, Sharmin (Journal of NELTA, 2012)
English as the foremost medium of international communication at present is called upon to mediate a whole range of cultural and cross-cultural concepts, to a greater extent than in the past. Inevitably human capital has taken a slant to fit in with the globalized world, and the notion of ‘Teaching English in a Cross-cultural Context’ is crucial. Hence, this paper focuses the possibilities and opportunities of multi-cultural education because of the global status of English. Exploring the challenges in teaching English in a cross-cultural context and the way to come out of the deficiency of the learners has been both obscure and controversial since long. What is widely accepted in this regard is English, not being the native language of the learners, triggers some problems. Therefore, the paper highlights core consideration for analyzing the challenges faced by the teachers and learners, and finally, recommends some directions to embrace the challenges. DOI: http://dx.doi.org/10.3126/nelta.v16i1-2.6135 NELTA 2011; 16(1-2): 114-122